Pengaruh Literasi Ekonomi terhadap perilaku konsumtif pada mahasiswa - Bayu Abadi; Sugeng Eko Putro Widoyoko; Cahyana Nursidiq (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2025)
This study aims to analyze the effect of economic literacy on students' consumer behavior through a comprehensive theoretical and empirical review. The method used is a qualitative literature review of 10 national scientific articles accredited by SINTA, sourced from Google Scholar and Garuda Ristekdikti databases publication range 2021–2025. The data analysis technique employs content analysis executed through four systematic stages: data reduction, data display theory verification/synthesis, and drawing conclusions. The results of the analysis show a significant and inversely proportional influence between the level of economic literacy and students' consumer behavior, where 9 out of 10 articles prove that higher economic literacy leads to a lower tendency for impulsive consumption among students.These findings discuss that economic literacy is effective in suppressing shopping behavior bias only if cognitive understanding is internalized into actual action, indicating the importance of reconstructing higher education curricula toward economic literacy learning based on applicative financial practices.